Interwoven : Andean lives in colonial Ecuador's textile economy - Corr, Rachel (The University of Arizona Press, 2018)
In the 1600s, Marcos Cunamasi, an indigenous man in Pelileo, Ecuador, hid his child to protect him from officials who would put the boy to work in the textile mill. Cunamasi was forced to turn him over. Because his young son couldn't keep up with spinning his quota of wool per day, Cunamasi helped so the child wouldn't be whipped. After working a year, Cunamasi was paid a shirt and a hat. Interwoven is the untold story of indigenous people's historical experience in colonial Ecuador's textile economy. It focuses on the lives of Native Andean families in Pelileo, a town dominated by one of Quito's largest and longest-lasting textile mills. Quito's textile industry developed as a secondary market to supply cloth to mining centers in the Andes; thus, the experience of indigenous people in Pelileo is linked to the history of mining in Bolivia and Peru. Although much has been written about colonial Quito's textile economy, Rachel Corr provides a unique perspective by putting indigenous voices at the center of that history. Telling the stories of Andean families of Pelileo, she traces their varied responses to historical pressures over three hundred years; the responses range from everyday acts to the historical transformation of culture through ethnogenesis. These stories of ordinary Andean men and women provide insight into the lived experience of the people who formed the backbone of Quito's textile industry.